Aspetti medico-legali dell’abuso sull’anziano - Fabbri Varliero, Giordano (Cultura giuridica e diritto vivente, 2018)
[Some medical-legal aspects of elder abuse] This study focuses on the phenomenon of abuse against older people, also called “elder abuse”. It follows on the main attempts devoted to defining this phenomenon and continues with an analysis of the types of abuse: physical, psychological, financial and neglect, as well they have been identified in legal-medical studies. Hence, it analyses the risk factors related to abuse and the signs that follow from it, to show the main characteristics of phenomenon and the signs preceding and succeeding the episodes of mistreatment. The last part of article concerns the US approach to the elder abuse treatment, consisting on creation of multidisciplinary groups and focusing on individual cases.